Experimental and predicted mechanical properties of Cr1−xAIxN thin films, at high temperatures, incorporating in situ synchrotron radiation X-ray diffraction and computational modelling. Issue 36 (20th April 2017) - Mohammadpour, Ehsan; Jiang, Zhong-Tao; Altarawneh, Mohmmednoor; Mondinos, Nicholas; Rahman, M. Mahbubur; Lim, H. N.; Huang, N. M.; Xie, Zonghan; Zhou, Zhi-feng; Dlugogorski, Bogdan Z.
Abstract : Cr1− x Al x N coatings, synthesised by an unbalanced magnetic sputtering system, showed improved microstructure and mechanical properties for ∼14–21% Al content. Abstract : Cr1− x Al x N coatings, synthesised by an unbalanced magnetic sputtering system, showed improved microstructure and mechanical properties for ∼14–21% Al content. In situ SR-XRD analysis indicated various crystalline phases in the coatings that included: CrN, AlN, α-Cr with small amounts of AlO2 and Al2 O3 over the 25–700 °C range. Al doping improves resistance to crystal growth, stress release and oxidation resistance of the coatings. Al doping also enhances the coating hardness ( H ) from 29 to 42 GPa, elastic modulus ( E ) from 378 to 438 GPa and increased the resistance to deformation. First-principles and quasi-harmonic approximation (QHA) studies on bulk CrN and AlN were incorporated to predict the thermo-elastic properties of Cr1− x Al x N thin film coatings in the temperature range of 0–1500 °C. The simulated results at T = 1500 °C give a predicted hardness of H = ∼41.5 GPa for a ∼21% Al doped Cr1− x Al x N coating.